Imaging the heart in pulmonary hypertension: an update - Grünig, Ekkehard; Peacock, Andrew J. (European respiratory review, 2015)
Noninvasive imaging of the heart plays an important role in the diagnosis and management of pulmonary hypertension (PH), and several well-established techniques are available for assessing performance of the right ventricle, the key determinant of patient survival. While right heart catheterisation is mandatory for establishing a diagnosis of PH, echocardiography is the most important screening tool for early detection of PH. Cardiac magnetic resonance imaging (CMRI) is also a reliable and practical tool that can be used as part of the diagnostic work-up. Echocardiography can measure a range of haemodynamic and anatomical variables (e.g. pericardial effusion and pulmonary artery pressure), whereas CMRI provides complementary information to echocardiography via high-resolution, three-dimensional imaging. Together with echocardiography and CMRI, techniques such as high-resolution computed tomography and positron emission tomography may also be valuable for screening, monitoring and follow-up assessments of patients with PH, but their clinical relevance has yet to be established. Technological advances have produced new variants of echocardiography, CMRI and positron emission tomography, and these permit closer examination of myocardial architecture, motion and deformation. Integrating these new tools into clinical practice in the future may lead to more precise noninvasive determination of diagnosis, risk and prognosis for PH.
Gesehen am 13.01.2021